2013
DOI: 10.4103/0973-1482.126446
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosin 1-phosphate contributes in tumor progression

Abstract: Sphingosine-1 phosphate (S1P) is a bioactive lipid that mediates diverse cellular responses. Signaling of S1P is carried out by a family of G-protein coupled receptors (GPCRs), which show differential expression patterns depending on tissue and cell types. Activation of S1P receptors induces signaling pathway, which can subsequently lead to physiological process. Intercellular S1P concentration is regulated and determined by several enzymes including S1P lyase, S1P kinase and S1P phosphatase. Numerous studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 140 publications
0
14
0
Order By: Relevance
“…S1P receptors are divided into five subtypes: S1PR1, S1PR2, S1PR3, S1PR4, and S1PR5, and S1PRs are differentially coupled to heterotrimeric G proteins and Rac or Rho to regulate various effectors, such as MAPKs 1, 14, 40, 41. Previous studies have shown that S1P‐SIPRs signaling can enhance cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1P receptors are divided into five subtypes: S1PR1, S1PR2, S1PR3, S1PR4, and S1PR5, and S1PRs are differentially coupled to heterotrimeric G proteins and Rac or Rho to regulate various effectors, such as MAPKs 1, 14, 40, 41. Previous studies have shown that S1P‐SIPRs signaling can enhance cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingosine‐1‐phosphate (S1P) is a bioactive sphingolipid metabolite involved in many pathophysiological processes 1, 2, 3, 4. The intracellular level of S1P as a secondary messenger 5 is regulated by several enzymes including anabolism and catabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, S1P levels were decreased in plasma of sepsis patients and animal models of ALI (Winkler et al, 2015; Zhao et al, 2011) and infusion of S1P offered protection against LPS- and CLP-mediated lung inflammation and injury (Szczepaniak et al, 2008). In other lung pathologies such as asthma, pulmonary hypertension, pulmonary fibrosis, bronchopulmonary dysplasia, and lung cancer, S1P levels are elevated in plasma and in lung tissues of patients and animal models (Gairhe et al, 2016; Harijith et al, 2013; Huang & Natarajan, 2015; Jolly, Rosenfeldt, Milstien, & Spiegel, 2002; Tabasinezhad et al, 2013). Blocking S1P production by inhibiting sphingosine kinase (SPHK) 1 and/or 2 seems to offer protection against lung inflammation and injury in several lung disorders (Ebenezer, Fu, & Natarajan, 2016; Huang & Natarajan, 2015; Natarajan et al, 2013).…”
Section: Modulation Of Lung Endothelial Barrier Function By Inflammatmentioning
confidence: 99%
“…Immune cells such as lymphocytes, hematopoietic progenitor cells, and dendritic cells employ the S1P gradient to regulate their trafficking [ 5 ]. S1P is also involved in tumor progression [ 6 ], neoplastic cell proliferation [ 7 ], migration [ 8 ], and resistance to chemotherapeutic drugs [ 9 ]. In some malignancies, S1P overexpression is associated with poor prognosis [ 10 ].…”
Section: Introductionmentioning
confidence: 99%